2005
DOI: 10.1029/2005gl023389
|View full text |Cite
|
Sign up to set email alerts
|

Electric fields and electron energies inferred from the ISUAL recorded sprites

Abstract: [1] Electron energies and the strength of electric fields in sprites are deduced for five selected events, which were recorded by the space-borne instrument called ISUAL (Imager of Sprites and Upper Atmospheric Lightning; a payload on the FORMOSAT-2 satellite). From the derived peak intensity ratios of spectrophotometer channel 2 (centered at 337 nm) and channel 3 (centered at 391.4 nm) of these sprites, the average and characteristic electron energies were found to be in the range of 6.2-9.2 eV and 4.5-6.5 eV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
153
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(165 citation statements)
references
References 23 publications
11
153
0
1
Order By: Relevance
“…Later on, the work by Morrill et al [2002] showed that the characteristic electron energies at altitudes below 55 km was ∼2.2 eV, while they reached a minimum of ∼1.75 eV at 60 km. More recent measurements (100 ms average) by the ISUAL instrument on board the FORMOSAT-2 satellite [Kuo et al, 2005] have shown that the average electron energies in the luminous regions of sprites are between 6.2 eV and 9.2 eV. This finding suggests that, in a first stage, electrons are capable of generating a considerable degree of excitation and ionization in the low-temperature air plasmas confined within the streamer tips and, consequently, an important number of atmospheric species can become chemically active through (initially) electron-driven reactions.…”
Section: Kinetic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Later on, the work by Morrill et al [2002] showed that the characteristic electron energies at altitudes below 55 km was ∼2.2 eV, while they reached a minimum of ∼1.75 eV at 60 km. More recent measurements (100 ms average) by the ISUAL instrument on board the FORMOSAT-2 satellite [Kuo et al, 2005] have shown that the average electron energies in the luminous regions of sprites are between 6.2 eV and 9.2 eV. This finding suggests that, in a first stage, electrons are capable of generating a considerable degree of excitation and ionization in the low-temperature air plasmas confined within the streamer tips and, consequently, an important number of atmospheric species can become chemically active through (initially) electron-driven reactions.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…The upper limit of the E/N values reported [Kuo et al, 2005] is in agreement with the electric field magnitudes (>3 E k /N) predicted in recent models of sprite streamers [Liu et al, 2006]. However, a more recent work [Adachi et al, 2008] using the blue to red (B/R) emission ratios observed by the dual-color array photometer (AP) of the ISUAL instrument indicates that the peak values of the reduced electric fields are 59-149 Td in the upper-diffuse region of sprites (above around 75 km) and 98-380 Td in the sprite lower-streamer-like region (below around 75 km).…”
Section: Kinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A streamer can initiate from a single electron avalanche at sprite altitudes and develop into a propagating ionization wave driven by a weak background electric field [Liu and Pasko, 2004, and references therein]. The inferred electric field derived from spectroscopic analysis [Kuo et al, 2005] or streamer modeling [Liu and Pasko, 2005;Liu et al, 2006] indicates a high electric field in the streamer head, which can trigger a series of chemical reactions. Sentman et al [2008] developed a plasma chemical streamer model (hereinafter referred to as S08) to quantify the local chemical effects for a passing sprite streamer at 70 km altitude.…”
Section: Introductionmentioning
confidence: 99%
“…The far-ultraviolet (FUV) emissions emitted by transient luminous events (TLEs) originated in the Lyman-Birge-Hopfield (LBH) band of nitrogen molecule N 2 . From the ISUAL data analyses, it is known that elves Kuo et al 2007Kuo et al , 2008Chang et al 2010), halos Kuo et al 2008), sprites (Kuo et al 2005Liu and Pasko 2005;Liu et al 2006), and gigantic jets (Kuo et al , 2009Chou et al 2010) are accompanied by FUV emissions. However, blue jets without the FUV emission were also reported (Chou et al 2010) as the longer life time of the N 2 LBH band upper state results in quenching at the lower altitudes.…”
Section: Introductionmentioning
confidence: 99%